The Toxins of Beauveria bassiana and the Strategies to Improve Their Virulence to Insects - Wang, Haiyang; Peng, Hui; Li, Wenjuan; Cheng, Peng; Gong, Maoqing (Frontiers in Microbiology, 2021)
The long-term and excessive usage of pesticides is an enormous burden on the environment which also increases pest resistance. To overcome this problem, research and application of entomopathogenic fungi, which are both environmentally friendly and cause lower resistance, have gained great momentum. Entomopathogenic fungi have a wide range of prospects. Apart from Bacillus thuringiensis, Beauveria bassiana is the most studied biopesticide. After invading insect hosts, B. bassiana produces a variety of toxins, which are secondary metabolites such as beauvericin, bassianin, bassianolide, beauverolides, tenellin, oosporein, and oxalic acid. These toxins help B. bassiana to parasitize and kill the hosts. This review unequivocally considers beauveria toxins highly promising and summarizes their attack mechanism(s) on the host insect immune system. Also, genetic engineering strategies to improve toxin principles, genes, or virulent molecules of B. bassiana have been discussed. Lastly, we discuss the future perspective of the Beauveria toxins research including newly discovered toxins.